Direct and one-pot conversion of polyguluronates and alginates into alkyl-l-guluronamide-based surfactant compositions. Issue 24 (12th October 2016) - Sari-Chmayssem, N.; Pessel, F.; Guégan, J. P.; Taha, S.; Mawlawi, H.; Benvegnu, T.
Abstract : One-pot transformation ofl -polyguluronates or alginates into 100% bio-based surfactants proceeded efficiently to provide novel long-chain alkyl-l -guluronamide/d -mannuronamide compositions as emulsion stabilizers. Abstract : We describe here an efficient one-pot process for the synthesis of 100% bio-basedl -guluronic acid based surfactant compositions as emulsion stabilizers, directly froml -polyguluronate or whole alginate, a renewable polysaccharide extracted from brown seaweeds. The transformation of these polymers into long-chain alkyl-l -guluronamides associated withd -mannuronamides when the alginate was used, has been achieved through the preparation of n -butyl uronate monosaccharide intermediates involving methane sulfonic acid-promoted hydrolysis, Fisher glycosylation and esterification reactions, followed by an in situ solvent-free aminolysis reaction with fatty amines.